Facilitating factors for seeking help for mental health problems among Norwegian adolescent males: A focus group interview study - Slotte, Sebastian; Ramsøy-Halle, Hege; Melby, Line; Kaasbøll, Jannike (Frontiers in Psychiatry, 2022)
Background: Young males are overrepresented in suicide statistics and underrepresented in statistics of help-seeking and receiving help from formal health services compared with young females. Few studies have examined facilitating factors for help-seeking among adolescent males with no previous experience seeking mental health help. This study aimed to explore thoughts, attitudes, and experiences regarding facilitating factors towards formal help-seeking for mental health problems among Norwegian adolescent males. Method: Three focus group interviews were conducted, each including four adolescent males with no experience with help-seeking or receiving help from a help service for mental health problems. The interviews addressed topics such as barriers and facilitating factors for help-seeking and preferences regarding structural factors and modes of delivery of help. Data were analysed according to the systematic text condensation method. Results: The analysis revealed three main categories of facilitating factors: 1) transparent information and available help services, 2) proactive and outreaching help services, and 3) the possibility for discreet help-seeking. Conclusions: Improving help-seeking is integral to accessing care and improving mental health. Help services can be more accessible and approachable for male adolescents if they offer discretion, the possibility to remain anonymous, the option to receive help in a convenient context, and outreach services.